Household incense burning and infant gross motor development: Results from the Taiwan Birth Cohort Study. (June 2018) - Wei, Chih-Fu; Chen, Mei-Huei; Lin, Ching-Chun; Guo, Yueliang Leon; Lin, Shio-Jean; Hsieh, Wu-Shiun; Chen, Pau-Chung
Abstract: Background: Air pollution from biomass burning were associated with neurodevelopmental deceleration, but limited studies concerned about the effect of indoor biomass burning. Incense burning is a common household ritual practice in Taiwan, while past studies mainly focused on birth weight and allergic disease. Objectives: We aimed to find the association between incense burning exposure and children's neurodevelopment. Methods: In Taiwan Birth Cohort Study (TBCS), a nationwide representative birth cohort study, children were assessed upon home interview with structured questionnaires upon six and eighteen months old. Multivariate logistic and Cox proportional hazard regression adjusting confounding factors were applied to explore the odds ratio (OR) and hazard ratio (HR) between household incense burning exposure and caregiver-reported neurodevelopment milestones. Results: In this study, 15, 310 term singletons were included, and household incense burning was associated with delay in gross motor neurodevelopment milestone, such as walking with support (Occasional incense burning: OR = 1.26, 95% confidence interval (CI): 1.08 to 1.47, HR = 1.07, 95% CI: 1.03 to 1.11; persistent incense burning: OR = 1.44, 95% CI: 1.22 to 1.69, HR = 1.11, 95% CI: 1.07 to 1.16) and walking steadily (Occasional incense burning: OR = 1.14, 95% CI: 0.98 to 1.32, HR = 1.07, 95% CI: 1.03 to 1.11, persistent incense burning: OR = 1.24, 95% CI: 1.06 to 1.45, HR = 1.09, 95% CI: 1.04 to 1.13). Conclusions: Our study suggested household incense burning exposure was associated with delay in gross motor neurodevelopmental milestones. Further research is warranted to elucidate the possible mechanism and causal relationship. Highlights: The effect of household incense burning on child neurodevelopment was not known. Household incense burning exposure was associated with delay in child gross motor development milestone achievement. The associations found above were more pronounced in persistent than ever exposed mother-infant pairs.